The role of information and financial reporting in corporate governance and debt contracting - Armstrong, Christopher S.; Guay, Wayne R.; Weber, Joseph P. (Journal of Accounting and Economics, 2010)
We review recent literature on the role of financial reporting transparency in reducing governance-related agency conflicts among managers, directors, and shareholders, as well as in reducing agency conflicts between shareholders and creditors, and offer researchers some suggested avenues for future research. Key themes include the endogenous nature of debt contracts and governance mechanisms with respect to information asymmetry between contracting parties, the heterogeneous nature of the informational demands of contracting parties, and the heterogeneous nature of the resulting governance and debt contracts. We also emphasize the role of a commitment to financial reporting transparency in facilitating informal multiperiod contracts among managers, directors, shareholders, and creditors.